Perkembangan Kristologi Abad Pertama Sampai Dengan Abad 5 - Hellen Candana Putri; Martha Tesalonika; Sarmauli, Sarmauli (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
Christology is the theological study of the person, nature, and work of Jesus Christ. This paper traces the development of Christology from the first century to the fifth century, highlighting the theological dynamics that took place in the early church. In the first century, Christology was based on the teachings of the apostles and the New Testament writings, with the main debate being over the humanity and divinity of Christ. The second and third centuries were characterized by the emergence of various theological schools, such as Gnosticism, Docetism, and Monarchianism, which prompted the church to affirm orthodox teachings. In the fourth century, the Council of Nicea (325 AD) and the Council of Constantinople (381 AD) played an important role in rejecting Arianism and affirming the oneness of Christ's essence with the Father. The fifth century witnessed more complex Christological debates, culminating in the Council of Ephesus (431 AD) and the Council of Chalcedon (451 AD), which established that Christ has two natures divine and human in one undivided person. This research confirms that the development of Christology in the first five centuries provided the foundation for Christian doctrine that continues to influence theological thought today.